Sosialisasi Pemanfaatan Artificial Intelegence (AI) pada Proses Pembelajaran di Madrasah Aliyah Bulukunyi - Nurqadriani; Muh. Nurfithri D.; Saharuddin; Yulianti (KHIDMAH: Jurnal Pengabdian Masyarakat, 2024)
This community service activity was conducted at MA Bulukunyi from May to July 2024, aiming to enhance students’ understanding and skills in utilizing AI in the learning process. Based on problem identification, it was found that student’s understanding of using AI in learning was still minimal. The methods used included training and workshop with several stages: preparation, implementation, and evaluation. In the preparation stage, need were identified through an initial survey and training materials were developed. The implementation stage involved delivering basic understanding of AI, using AI-based applications, demonstrating AI application in education, and holding discussion forums. Evaluation was carried out through direct observation and feedback questionnaires. The result showed that student were highly engaged in the training process, with high active participation in answering and asking questions and expressing opinions. Feedback questionnaires indicated high satisfaction with the relevance of the materials, quality of delivery, relevance to practical application, and training facilities. In conclusion, this activity successfully increased students’ engagement and understanding of AI. Recommendations for further development include improving training facilities and providing advanced training to deepen students’ knowledge.